Semiotyczne aspekty virtual reality - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
The dynamic development of virtual reality technics opened new possibilities of creating visual, audial and audiovisual moving pictures. VR is coming and invaiding XXIst century cinema. There is a grand challenge for filmmakers imagination: show delivering vision of reality or so-called reality made without using real physical objects. Are we really prepared for this technological revolution? Hendrykowski’s paper poses certain crucial questions connected with that change in making movies. Among them: ambigous nature of digital sign, possible regions of spectator’s new experiences, symbolic function of digital images and deep transformation of category od aesthetics in expanding world of multimedia.